PENGARUH TEKNIK RELAKSASI TERHADAP ADAPTASI NYERI PERSALINAN IBU BERSALINKALA I FASE AKTIF DI BPS WILAYAH PUSKESMAS PATRANG KABUPATEN JEMBER TAHUN 2012 - Moh. Wildan; Yuniasih Purwaningrum (Jurnal Ilmu Kesehatan Masyarakat, 2013)
In the first stage of labor uterine contractions that cause pain stimuli, approximately 90% of labor is accompanied by pain. Efforts to reduce or eliminate non-pharmacological pain in childbirth with hypnosis, reduce the perception of pain, cutaneous stimulus and Relaxation Techniques. Relaxation techniques are external actions that affect the internal response of the individual. This study aims to determine the effect of relaxation techniques to adaptation of the first stage of labor pain in the active phase of Public health centers in the district Patrang Jember. The research design was pre Experiment (Quasi experiment) by the method of a "One-Group Pre-test - Post test Design". Samples were 30 respondents, the selection of samples using non-probability sampling technique (Accidential sampling). Data collected by observation intensites pain before and 30 minutes after the technique of relaxation. Data analysis ststistik using Wilcoxon  Mafched Pair Test, with a significance level (df 5%).The results Z count -5.203 was greater than -1.96. Thus Ho is rejected, mean relaxation techniques affect the adaptation of labor pain in the active phase of the first stage in the Public health center Patrang Jember district. Seeing the results of this study provide innovation Midwife charged with using the latest methods to perform care dear mother, one of which is the method of relaxation techniques. A mother has the right to obtain delivery of high quality care delivery so as to avoid inconvenience at the time of delivery.